Knowledge management readiness measurement: case study at institution of higher learning in Malaysia - Mohamed Razi, Mohamed Jalaldeen; Nor Shahriza, Abdul Karim; Norshidah, Mohamed (2011)
An evaluation on organizational readiness for knowledge management (KM) process implementation is recommended before embarking on actual implementation. This study aims to measure the perceived KM readiness of a Malaysian higher education institution and to find the contributing factors of it. A model was developed and hypotheses were formulated. Data were collected from a sample of 46 academic staff using a survey. The findings shows that the institution is ready for KM process implementation, but only organizational strategy, ICT use, and performance expectancy of KM were became significant contributing factors out of seven factors proposed in the model. This study can be considered as the starting point for future studies in this area of KM and the proposed research framework might be applied in different settings and context to make it a robust.